The Impact of the Safe and Successful Youth Initiative (SSYI) on City-Level Youth Crime Victimization Rates - Anthony Petrosino; Herbert Turner; Thomas Hanson; Trevor Fronius; Patricia Campie; Cailean Cooke (Journal of MultiDisciplinary Evaluation)
Background: The physical, emotional, and financial costs resulting from youth violence are well documented.